Adaptive integral-sliding-mode control strategy for maneuvering control of F16 aircraft subject to aerodynamic uncertainty - Ijaz, Salman; Fuyang, Chen; Hamayun, Mirza Tariq; Anwaar, Haris (Applied mathematics and computation, 2021)
•This research emphasizes on an adaptive nonlinear integral-sliding-mode (ISM) controller design for F16 aircraft. The objective is to attain the desired maneuvering subject to the unknown external disturbance and aerodynamical uncertainty effects.•The nonlinear dynamics of F16 aircraft is first partitioned into inner faster and outer slower loop. For each loop, the adaptive ISM control strategy is proposed where the baseline controller is designed using nonlinear-dynamics-inversion (NDI technique)•The aerodynamics coefficients, that are the nonlinear function of angle-of-attack α, and side slip angle β, are estimated using iterative reweighted least square algorithm. The estimated information is available to the controller design where the estimation error is treated as unmatched uncertainty.•A detailed analysis is performed to show that the aircraft internal dynamics are stable for the applicability of NDI controller.•A detailed comparison is performed with NDI controller and ISM/NDI controller to validate the dominant performance of proposed scheme. Aircraft dynamics are highly nonlinear and the traditional linear flight controllers cannot fully utilize the real-time performance ability of aircraft. This paper investigates a nonlinear control approach for high maneuvering fighter aircraft that deployed baseline nonlinear-dynamics-inversion (NDI) control and high-level robust adaptive integral-sliding-mode (ISM) control. The design objective is to maintain the acceptable flight quality at a high angle-of-attack under the influence of unknown disturbance and aerodynamics uncertainties. The nonlinear dynamics of F16 aircraft are divided into two loops by utilizing time-scale separation principle and adaptive ISM/NDI controller is designed for each loop. The aerodynamics coefficients are estimated using the iterative reweighted least square (IRLS) algorithm based on the wind tunnel real-time flight data available at NASA Langlet and Ame Research center. The internal dynamics stability is proven to validate the complete system stability. Simulations are conducted on F16 aircraft and compared the results with the NDI controller and ISM/NDI controller (without adaptive strategy).